Entosis: The emerging face of non-cell-autonomous type IV programmed death [Image: see text] - Martins, Isabelle (Biomed J, 2017)
The present review summarizes recent experimental evidences about the existence of the non-cell-autonomous death entosis in physiological and pathophysiological contexts, discusses some aspects of this form of cell death, including morphological, biochemical and signaling pathways that distinguish non-cell-autonomous demises from other death modalities and propose to define this new modality of death as type IV programmed cell death.